PENYULUHAN DAN PENDAMPINGAN PENGOLAHAN KOTORAN TERNAK SAPI DI DUSUN MONGGE-2 MENJADI PUPUK ORGANIK PADAT - Dewi, Suprayanti Martia; Nikmatullah, Aluh; Sarjan, Muhammad; Kisman, Kisman; Haryanto, Hery; Jihadi, Amrul (Jurnal Pepadu, 2024)
Mongge-2 Hamlet, one of the hamlets in the Penyangga Village area. Services activity accompanied by assistance in processing livestock manure to produce organic fertilizer to support sustainable integrated farming system in this hamlet. The aim is to empower the community with productive activities through optimizing the potential of natural resources and human resources by involving relevant stakeholders. This service activity will be carried out in 2023, starting with a location survey activity. The next activity is coordinated to determine target communities to be given regular counseling and assistance to produce solid organic fertilizer and how to apply it in the field. After the outreach and mentoring activities are carried out, monitoring, reporting and publication are carried out. The organic fertilizer produced is applied to garden and agricultural cultivation around Mongge-2 Hamlet. This organic fertilizer is expected to play a role in improving the soil and is expected to reduce the use of synthetic fertilizers and increase the fertility of the media used. so that agricultural products are healthier for consumption. Further research needs to be carried out to determine the content of the organic fertilizer produced and its effect on the growth of agricultural cultivation of certain commodities.